Innovation in Supply Chain Finance as a New Alternative Financing Means for Russian Enterprises - Christian Agbatchi ODE; Motorina Irina Ivanovna; Yunusova Leisen Damirovna; Ajdar Airativich Ajupov (International Journal of Supply Chain Management, 2020)
Abstract— This article discusses the access of enterprises to financial supply chain services in the Russian Federation. Based on the analysis of SME financing history, we deduce the difficulties for SMEs to access the bank financial services since their emergence in spite of their important role in the country's development process. Indeed, alternative sources of credits such as crowdfunding offer a new opportunity to SMEs. Crowdfunding removes the barriers of the process duration, the barriers related to application fees, and allow smart contracts between different investors and SMEs to be obtained very quickly. While spreading the risk of the project between investors, crowdfunding is risky for investors. Innovation in supply chain finance is about the ability to meet the greatest challenges of a business with an approach that is at once meticulous in its attention to detail, and boundless in its creativity.